Data from: Small Carbonaceous Fossils (SCFs) from North Greenland: new light on metazoan diversity in early Cambrian shelf environments ... - Wallet, Elise; Slater, Ben; Willman, Sebastian; Peel, John (Dryad, 2020)
The Sirius Passet Lagerstätte of North Greenland provides one of the oldest records of soft-bodied metazoan-dominated ecosystems from within the early Cambrian. The Lagerstätte site itself is restricted to just a single ~1 km-long outcrop located offshore from the shelf margin, in an area that has been affected by metamorphic alteration during the Ellesmerian Orogeny (Devonian–Early Carboniferous). The recent recovery of Small Carbonaceous Fossils (SCFs) to the south in areas that have escaped the effects of this deformation has substantially expanded the known coverage of organic preservation into shallower-water depositional settings in this region. Here we describe additional SCF assemblages from the siliciclastic shelf succession of the Buen Formation (Cambrian Series 2, Stages 3-4; ∼ 515 Ma), expanding upon the previously documented SCF biota. Newly recovered material reveals a rich diversity of non-mineralizing metazoans, chiefly represented by arthropod remains. These include the filtering and ... : SCF extraction and study techniques follow those outlined in Butterfield and Harvey (2012). About 50g of each sample was macerated in hydrofluoric acid to recover organic residues. Individual SCFs were hand-picked and mounted for light microscopy. Figured specimens are deposited in the Museum of Evolution, Uppsala, Sweden. ...